Capacity Development Strategies for Village Apparatus in Improving The Quality of Public Services in Villages Within The Administrative Area of Sumowono Subdistrict, Semarang Regency - Sutrisno, Sutrisno; Wahyu Murti (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the capacity building strategies for village officials in improving the quality of public services in the administrative area of Sumowono District, Semarang Regency. Capacity development of village officials is a key factor in effective village governance and quality service delivery to communities. This study employed a descriptive qualitative method with data collection through interviews, observations, and documentation studies in five sample villages in Sumowono District. The results show that the capacity development strategies implemented include administrative technical training, mentoring, technical guidance, and village information system development. Supporting factors for capacity development include local government commitment, budget support, and village apparatus participation, while inhibiting factors identified include infrastructure limitations, educational background differences among officials, and personnel turnover. This research recommends strengthening continuous training programs, improving inter-institutional coordination, and enhancing monitoring and evaluation systems to ensure the effectiveness of village officials' capacity development.